Counter-attitudinal exemplars viewed through the social identity lens: a case of climate change and political partisans - Morris, Jessica R., author; Christen, Cindy, advisor; Anderson, Ashley, committee member; Lacy, Michael, committee member (Colorado State University. Libraries, 2017)
This study examined the relationship between social identification theory and exemplification theory through the use of counter-attitudinal exemplars. Exemplification theory predicts that inferences from one single exemplar will be made for an entire group. Social identity theory states that members of groups act in accordance with the group's norms. Therefore, a combination of the two theories predicts that an exemplar from a group will cause the audience to project the exemplar characteristics on the larger group, thus causing in-group and out-group members to re-evaluate the group. Using Democrats and Republicans as the groups and climate change as the attitude issue, this study aimed to understand how people in social groups respond to exemplars that are counter-attitudinal to the group's traditional values. A 2 x 2 x 2 factorial design was created to manipulate the variables of political partisanship of the exemplar (Democrat or Republican), attitude expressed (pro- or anti-climate change), and political partisanship of the participant (Democrat or Republican). Three-hundred-and-twenty-five participants took both pre- and post-tests in order to gauge their identification with the exemplar and attitude change after viewing the stimulus material. Results showed that participants were willing to change attitude about the exemplar, but had no change in attitude toward climate change (regardless of political affiliation). Article slant had a main effect on participants' attitudes towards the exemplars in addition to an interaction effect between article slant and participant political party identification. The party of the exemplar did not have an effect on the participants' attitudes toward climate change. The researcher concluded that climate change attitudes are difficult to influence, regardless of participant stance and political identification. However, the statistically significant findings gave some new theoretical implications for social identity theory research. The interaction effect of political party and slant of the article suggested that social identity theory influenced participants' attitudes about the exemplar. When an exemplar from the participants' group negatively or positively exemplified the group's views on climate change, the participant had a greater attitude change about the exemplar than someone that was not part of the exemplar's political group. The main effect of article slant also had important implications—participants were willing to change attitude about an exemplar based on the exemplar's attitude about climate change. Therefore, political figures can significantly bolster or damage their reputation based on their attitudes about climate change. Finally, this study found some areas in social identity theory that need some additional research. The majority of the Republican participants in this study were pro-climate, and therefore were group deviants. Therefore, their responses reflected the attitudes of how deviant members evaluate members of their in-group. This study concluded that deviant members have higher evaluations of deviant exemplars. Upon searching, there was not significant research done in deviant group members' evaluations of other deviants. Future research should be conducted to better understand how deviant and marginalized group members rationalize group membership.